МОДЕЛЮВАННЯ РЕЖИМІВ РОБОТИ ГІБРИДНИХ ФІЛЬТРОКОМПЕНСУЮЧИХ ПЕРЕТВОРЮВАЧІВ ПРИ ЗАБЕЗПЕЧЕННІ ЕЛЕКТРОМАГНІТНОЇ СУМІСНОСТІ В ТРИФАЗНИХ СИСТЕМАХ - Жаркін, А.Ф.; Новський, В.О.; Малахатка, Д.О. (Інститут електродинаміки НАН України, Київ, 2022)
In the article are considered the main aspects of the use of the developed hybrid filter compensating converters(GFCC), which are based on a regulated filtering device and a "distributive" static synchronous reactive power compensator for complex improvement of the electric power quality and provision of electromagnetic compatibility in local power supply systems. GFCC are designed to compensate the load currents in the neutral conductor of a three-phase low-voltage network, symmetrical regulation (stabilization) voltage of the load and filtering the currents of higher harmonics at the terminals of responsible consumer in the local network. References 3, figures 3, table 1.